2020
DOI: 10.1128/aem.01595-20
|View full text |Cite
|
Sign up to set email alerts
|

Dead-End Ultrafiltration and DNA-Based Methods for Detection of Cyclospora cayetanensis in Agricultural Water

Abstract: Cyclospora cayetanensis is a protozoan parasite that causes foodborne and waterborne diarrheal illness outbreaks worldwide. Most of these outbreaks are associated with consumption of fresh produce. Sensitive and specific methods to detect C. cayetanensis in agricultural water are needed to identify the parasite in agricultural water used to irrigate crops that have been implicated in outbreaks. In this study, a method to detect C. cayetanensis in water by combining dead-end ultrafiltration (DEUF) with sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Eimeria acervulina is intriguing as a surrogate because it poses no occupational safety risk to researchers, it has a low infectious dose, and is relatively easy to passage in vivo and produce many oocysts. Although sensitive methods exist to detect C. cayetanensis oocyst contamination in food and water matrices [59][60][61][62], a means to determine oocyst viability (and thus, infection risk oocysts pose to public health) remains elusive. Our transcriptome analysis is ideal for addressing this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria acervulina is intriguing as a surrogate because it poses no occupational safety risk to researchers, it has a low infectious dose, and is relatively easy to passage in vivo and produce many oocysts. Although sensitive methods exist to detect C. cayetanensis oocyst contamination in food and water matrices [59][60][61][62], a means to determine oocyst viability (and thus, infection risk oocysts pose to public health) remains elusive. Our transcriptome analysis is ideal for addressing this issue.…”
Section: Discussionmentioning
confidence: 99%
“…There were 21 C. cayetanensis -positive samples: 13 from wildlife feces, 7 from soil, and 1 from water, giving the impression that the parasite may be more frequent in the USA than formerly considered and could be transferred by wildlife as paratenic hosts. The parasite was also detected in surface water samples in the Chesapeake and Ohio Canal (C&O Canal) in Maryland [ 41 , 42 ]. In Florida, cyclosporiasis was linked to gardening and working with soil [ 43 ].…”
Section: Cyclosporiasis Situation In Epidemic Areas: Potential For En...mentioning
confidence: 99%
“…Additionally, this scoping review revealed an absence of detection-method studies on soil and only two studies on water. In 2019, a validated method for detecting C. cayetanensis in water was accepted as a standard method by the FDA [44].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Additionally, this scoping review revealed an absence of detection-method studies on soil and only two studies on water. In 2019, a validated method for detecting C. cayetanensis in water was accepted as a standard method by the FDA [44]. Pertinently, a recent Blue-Ribbon Panel report indicated a need for the development of detection methods for C. cayetanensis in environmental samples [45].…”
Section: Summary Of Evidencementioning
confidence: 99%